1969
DOI: 10.3382/ps.0481055
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Steam Pelleting on the Utilization of Phosphorus by the Laying Hen

Abstract: S UMMERS et al. (1967) reported that commercial steam pelleting resulted in enhanced utilization of dietary phosphorus from plant origin when fed to young growing chickens. Considering the relatively high level of phytin or organic phosphorus present in most poultry diets and the fact that a large percentage of poultry feed is being steam pelleted the economic importance of such a finding is readily apparent. For the laying hen phosphorus from plant origin is usually considered to be around 50% available. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1976
1976
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The results also demonstrated that a ration containing no IP, 0.10% AP and 0.30% TP was not satisfactory for laying hens. For the most part, the data agree with the findings of Pepper et al (1959) and Pepper et al (1969) and Hunt and Chancey (1970) in the low levels of P can fulfill die hen's requirement. Pepper et al (1959) and Pepper et al (1969) also reported that the P requirement of hens could be fulfilled by rations in which all P was of plant origin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results also demonstrated that a ration containing no IP, 0.10% AP and 0.30% TP was not satisfactory for laying hens. For the most part, the data agree with the findings of Pepper et al (1959) and Pepper et al (1969) and Hunt and Chancey (1970) in the low levels of P can fulfill die hen's requirement. Pepper et al (1959) and Pepper et al (1969) also reported that the P requirement of hens could be fulfilled by rations in which all P was of plant origin.…”
Section: Discussionsupporting
confidence: 91%
“…The National Research Council (1971) recommended a dietary P level of 0.6% and indicated that a portion of this P should be in organic form. Vohra et al (1974) reviewed the literature and suggested that 0.4% P in laying hen rations was adequate but gave no indication as to sources of the P. Since Pepper et al (1959) reported that rations containing 0.38% P, all of plant origin with 0.11% as non-phytin P, were adequate for laying hens, several papers have been published indicating that the hen's P requirement is less than that recommended by the National Research Council (1971) (Pepper et al 1969;Hunt and Chancey, 1970;and Summers et al, 1976). However, Waldroup et al (1967), Garlich et al (1975) and Garlich and Parkhurst (1976) found that levels of 0.34 to 0.44% P were not satisfactory for maintaining high rates of egg production and health of the hens.…”
mentioning
confidence: 96%
“…There are also many reports indicating that dietary phosphorus levels below those normally used in commercial rations can be fed to laying hens without detrimental effects on performance (Pepper et al, 1969;Damron et al, 1974;Summers et al, 1976;Scott etal, 1976;Edwards and Suso, 1981;Mikaelian and Sell, 1981). Furthermore, a number of investigators have reported that low levels of phosphorus improved shell quality (Hunt and Chancey, 1970;Scott et al, 1976;Garlich, 1979).…”
Section: Introductionmentioning
confidence: 89%